Efecto del tiempo de cocción y la concentración de mashua negra (Tropaeolum tuberosum) en la aceptabilidad de un pionono - Chavarri Julcamoro, Fairus Dayan (2019)
Effect of cooking time and concentration of black mashua (Tropaeolum tuberosum) on the acceptability of a pionono. The process of elaboration of the pionono consisted of weighing all the inputs separately according to the list of ingredients and beat for two minutes at medium speed adding the flours according to the experimental design. Then the mass of 850 grams was weighed and standardized in the trays which were previously covered with paper. It was then baked at 200 ° C for a period of time according to the statistical design. Finally it was filled with cream and rolled to give it the proper shape. A Rotational Central Composite Design (DCCR) of two (2) independent variables was used, which were the cooking time (1 to 6 minutes) and the concentration of black mashua flour (3 to 9%) making a total of 11 trials. The response variable was the general acceptability of the product. Sensory analysis was performed with a panel of 90 panelists where the general acceptability of the pionono was evaluated; taking into account that each panelist had to evaluate a maximum of 6 samples at a time. The STATISTICA 7 program was used to analyze all the data. The cooking time had a greater effect on the acceptability of the product while the replacement of black mashua flour had no influence on the pionono. With a cooking time between 3.5 and 5 minutes and a substitution of black mashua flour between 5 and 7%, greater acceptance was obtained by consumers.